2017
DOI: 10.21470/1678-9741-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c Levels Predicts Acute Kidney Injury after Coronary Artery Bypass Surgery in Non-Diabetic Patients

Abstract: Introduction Elevated hemoglobin A1c levels in patients with diabetes mellitus have been known as a risk factor for acute kidney injury after coronary artery bypass grafting. However, the relationship between hemoglobin A1c levels in non-diabetics and acute kidney injury is under debate. We aimed to investigate the association of preoperative hemoglobin A1c levels with acute kidney injury in non-diabetic patients undergoing isolated coronary artery bypass grafting.Methods202 non-diabetic patients with normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Third, we did not use urine output for diagnosis of AKI that might lose some cases according to the existing definitions. Forth, we did not measure hemoglobin A1C to differentiate poor from well-controlled diabetes in both diabetics and non-diabetics that can affect the development of AKI as reported by Kocogulları et al [ 31 ] , suggesting an association between preoperative level of Hb A 1C and development of AKI in non-diabetics.…”
Section: Discussionmentioning
confidence: 94%
“…Third, we did not use urine output for diagnosis of AKI that might lose some cases according to the existing definitions. Forth, we did not measure hemoglobin A1C to differentiate poor from well-controlled diabetes in both diabetics and non-diabetics that can affect the development of AKI as reported by Kocogulları et al [ 31 ] , suggesting an association between preoperative level of Hb A 1C and development of AKI in non-diabetics.…”
Section: Discussionmentioning
confidence: 94%
“…In line with Oezkur et al [17] , we also noted that diabetes was an independent risk factor for AKI. Interestingly, Kocogulları et al [25] suggested an association between preoperative level of Hb A 1C and the development of AKI in non-diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, optimizing the transfusion strategy shall be considered in the upcoming clinical trials. Several available therapeutic options to reduce the harm of erythrocyte on CSA-AKI patients were studied [23,25] . Interventions reducing perioperative hemodilution by minimizing fluid administration and retrograde autologous priming of the cardiopulmonary circuit, salvage of shed blood, and tolerance of moderate hemodilution can be easily applied.…”
Section: Discussionmentioning
confidence: 99%